EFFICACY OF INSECTICIDES ON SEED ALFALFA IN THE SECOND YEAR OF LIFE - Andrii TYSHCHENKO; Olena TYSHCHENKO; Olena PILIARSKA; Tetiana MARCHENKO; Kateryna FUNDIRAT; Viktor SHARII; Vira KONOVALOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the study was to study the effectiveness and provide an economic assessment of the use of various insecticides against pests on alfalfa seed crops in the second year of the grass stand. The research was conducted during 2019–2021 at the experimental field of the Institute of Irrigated Agriculture of the NAAS. Treatment with insecticides was carried out: the first – in the phase of the beginning of budding, the second - before the beginning of flowering. The use of insecticides reduced the number of pests on the grass stand. The most effective in the fight against pests (with the exception of Aphis craccivora Koch) was the preparation with the active substances Chlorpyrifos, 500 g/l and Cypermethrin, 50 g/l and the consumption rate of 1.00 l/ha. The highest seed yield was obtained in the first treatment with an insecticide preparation with the active substances Chlorpyrifos, 500 g/l and Cypermethrin, 50 g/l and the consumption rate of 1.00 l/ha, and in the second treatment with preparations with the active substances Chlorantraniliprole, 200 g/l and Lambda-cyhalothrin, 50 g/l at a rate of 0.17 and 0.15 l/ha, respectively. When irrigated with this variant, the seed productivity was 635.2 kg/ha, which was higher than the control variant by 115.3 kg/ha. Under conditions of natural moisture, the seed yield was 452.5 kg/ha, and was higher than the control by 74.3 kg/ha. The lowest cost price of 0.66 €/ha and the highest conditional net profit of 1702.87 €/ha was obtained on the option: the first treatment - Chlorpyrifos, 500 g/l and Cypermethrin, 50 g/l, the second – Chlorantraniliprole, 200 g/l and Lambda-cyhalothrin, 50 g/l.